PRICE SENSITIVITY ANALYSIS ON PURCHASING DECISION PROCESS OF DURIAN IN JEPARA REGENCY AND SEMARANG CITY CENTRAL JAVA - Nida, Khofiatun; Ekowati, Titik; Santoso, Siswanto Imam (Tadulako University, 2018)
Uncertainty of harvested area and the amount of durian production each year makes the price of the durian tend to fluctuate. Price changes can trigger price sensitivity at the consumer level. This study aimed to analyze the level of durian price sensitivity in Jepara Regency and Semarang City and analyze the factors that make the process of buying durian in Jepara Regency and Semarang City. The analysis used in this research was descriptive analysis and logistic regression analysis. The price suggests that the price of Jepara Regency and Semarang City is IDR 45,000.00 â 50,000.00. Overall price levels received durian consumers in the Semarang City was higher than Jepara Regency. Based on the results of logistic regression analysis, it is known that simultaneously the price factor, income, occupation, age, taste, shape, size, aroma, color. and size.